AI-POWERED PREDICTIVE ANALYTICS IN EMERGENCY MEDICINE: REDUCING RESPONSE TIME AND IMPROVING OUTCOMES - Istamov Mirjahon Mo'minjon o'g'li (TADQIQOTLAR, 2025)
Abstract: The application of artificial intelligence (SI) technologies in the field of emergency medicine makes it possible to radically change the quality of medical services. Artificial intelligence-based predictive analysis plays a particularly important role in reducing response time and improving outcomes. In emergency situations, every second is calculated, so there is a need to make quick and clear decisions. With the help of advanced AI algorithms and the ability to analyze large amounts of data, the effectiveness of emergency medical care processes is increased.